Identification of sixteen peptides reflecting heat and/or storage induced processes by profiling of commercial milk samples - Ebner, Jennifer; Baum, Florian; Pischetsrieder, Monika (Journal of Proteomics, 2016)
Peptide profiles of different drinking milk samples were examined to study how the peptide fingerprint of milk reflects processing conditions. The combination of a simple and fast method for peptide extraction using stage tips and MALDI–TOF–MS enabled the fast and easy generation and relative quantification of peptide fingerprints for high-temperature short-time (HTST), extended shelf life (ESL) and ultra-high temperature (UHT) milk of the same dairies. The relative quantity of 16 peptides changed as a function of increasing heat load. Additional heating experiments showed that among those, the intensity of peptide β-casein 196–209 (m/z 1460.9 Da) was most heavily influenced by heat treatment indicating a putative marker peptide for milk processing conditions. Storage experiments with HTST- and UHT milk revealed that the differences between different types of milk samples were not only caused by the heating process. Relevant was also the proteolytic activity of enzymes during storage, which were differently influenced by the heat treatment. These results indicate that the peptide profile may be suitable to monitor processing as well as storage conditions of milk.
Keywords: Milk; MALDI–TOF–MS; Peptide profiling; Processing marker; Storage marker; Heat treatment